Severe acute malnutrition and infection - Jones, Kelsey D J (Paediatr Int Child Health, 2014)
Severe acute malnutrition (SAM) is associated with increased severity of common infectious diseases, and death amongst children with SAM is almost always as a result of infection. The diagnosis and management of infection are often different in malnourished versus well-nourished children. The objectives of this brief are to outline the evidence underpinning important practical questions relating to the management of infectious diseases in children with SAM and to highlight research gaps. Overall, the evidence base for many aspects covered in this brief is very poor. The brief addresses antimicrobials; antipyretics; tuberculosis; HIV; malaria; pneumonia; diarrhoea; sepsis; measles; urinary tract infection; nosocomial Infections; soil transmitted helminths; skin infections and pharmacology in the context of SAM. The brief is structured into sets of clinical questions, which we hope will maximise the relevance to contemporary practice.